Comparative Analysis of Educational Resource Management Models - Ritonga, Irma; Rizki, Annisa; Manintin, Chardo; Pulungan, Lilik Hidayat (Lembaga Riset Mutiara Akbar, 2024)
The aim of this research is a comparative analysis of educational resource management models. Educational resource management Refers to the context and factors that influence how educational resources are managed and utilized to achieve set educational goals. In its application, the educational resource model involves evaluating and comparing various approaches, methods or strategies in management, development and utilization of resources to achieve educational goals. The education system in Indonesia has formal, non-formal and informal education systems, and existing educational support must be able to provide adequate educational resources. In writing this article, the library study or library research approach is used, where the researcher collects research-related materials from books, magazines, scientific works, literature, mass media reports, etc., then describes and explains the data.